Mechanisms of atopic dermatitis and allergy development in African (AmaXhosa) children between 12-36 months of age - Lunjani, Nonhlanhla (Department of Medicine, 2025)
Atopic dermatitis is a highly complex multifactorial inflammatory skin disease that disproportionately affects children and has increased rapidly during recent years in South Africa. Current data suggest that the changing diversity of environmental exposures, diet, and lifestyle factors across African societies might provide unique disease promoting effects in populations where a low risk of developing AD and allergic disease was previously documented. To identify novel immunological endotypes and responsible environmental exposures in South African children with AD, we collected data on environmental exposures, lifestyle factors, and conducted clinical assessments in 217 children (Urban AD, n=56; Rural AD, n=60; Urban Healthy Controls, n=49; Rural Healthy Controls, n=52). Detailed immunological analysis (cell counts, cytokine levels, serology and RNA-Seq) were performed on 152 of these children. Participants were from the same ethno-linguistic AmaXhosa background. Strong evidence for persistent TH2 responses (elevated circulating eosinophils, allergen-specific IgE, TARC, MCP-4, and IL-16 levels) with reduced TH17 responses (IL-17A and IL-23 levels) were seen in South African children with AD regardless of whether they lived in urban or rural communities. However, independent of AD, a vast array of circulating immune mediators (including proinflammatory cytokines, chemokines, soluble adhesion molecules and growth factors) were associated with early life nutrition, medications, animal exposures, indoor environment, sunlight exposure and household size. RNA sequencing of peripheral blood mononuclear cells corroborated the TH2 cytokine profile identified. Furthermore, multiple immunological pathways (including immunoregulatory factors, aryl hydrocarbon receptor and G protein-coupled receptors) were discovered to be differentially expressed in rural and urban children, regardless of atopic status. The study results address knowledge gaps on the immune interactions between atopic dermatitis and environmental exposures in South African children and clarify population-specific AD endotypes. Overall, protective exposures (e.g., animal) and potentially detrimental (e.g., pollutant) exposures shape the early life innate and adaptive immune response. Lastly, when immune-mediated disorders do occur in children, living environment is worth considering and its effects on background immune profile that can potentially interact with immune-targeting therapies and consequently impact treatment efficacy.